Gaining a face : the romanticism of C.S. Lewis - Prothero, James; Williams, Donald T. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2013)
Contrary to the popular perception that C.S. Lewis was merely a religious writer, there is a good case to be made for Lewis being one of the major British writers of the twentieth century if we look at him as a prime member of a resurgent Romantic movement after the Second World War. Much has been written on Lewis's thoughts on joy, a central aspect of his Romanticism. However, Lewis was at the same time a Rationalist, and managed to merge his rationalism with his romanticism in a unique and original manner. And his romanticism likewise was complex and owed much to George MacDonald and, through medium of McDonald's thought, to the romanticism of William Wordsworth.
Romanticism and C.S. Lewis -- Beauty, Wordsworth, and Lewis -- The romantic roots, Woodsworth and Coleridge -- MacDonald, Chesterton, and Barfield -- The Prelude, Wordsworth, and Lewis -- Perelandra and the Space Trilogy: creation and the medieval utopia in Lewis's vision -- surprised by Joy and the redemption of nature -- Early and late: the pilgrim's regress to till we have faces -- Lewis as child critic -- Leavis, Lewis, and postmodernism.
Keywords: Lewis, C. S. -- 1898-1963 -- Criticism and interpretation